Desarrollo de un sistema de consumo de datos, empleando prácticas ágiles, para el registro de la propiedad y jefatura de avalúos y catastros del Gadm Muisne - Chuqui Balarezo, María José (2022)
This technological proposal was carried out in the Autonomous Decentralized Municipal Government of Muisne, departments of the property registry and the head office of appraisals and cadaster, located in the province of Esmeraldas in the canton of Muisne, in the lack of coordination between the two departments leads to a disorganization of the cadastral procedures, purchase and sale of properties, property registrations presented by the common users, as different processes are required to access these procedures, the objective of the technological proposal is to develop a data consumption system to manage the information in a single system and not separately with the use of agile practices, for the development of the project the methodologies of qualitative and quantitative research, bibliographic and data collection instruments such as interview and survey were used in order to identify the main needs, software tools were applied, such as Python language, Django Framework, SQL Server, Git, Visual Studio Code development IDE, also an architecture based on MVC was applied, using the agile practice SCRUM, obtaining as a result the union of the two departments, by means of a system that manages the information of these departments. Thus, it is concluded that, by implementing the data consumption system in the two departments, the procedures with the users of the canton were optimized, increasing the satisfaction of the four civil servants of these departments of the GADM.